PENERAPAN RESTORATIVE JUSTICE SEBAGAI UPAYA MELINDUNGI KORBAN KEKERASAN SEKSUAL - Mahbub, Moh (Jurnal Media Justitia Nusantara, 2022)
Sexual violence is a grave global issue impacting numerous individuals. This research aims to examine restorative justice's concept, the impact on sexual violence victims, and explore its application for their protection. The normative juridical research method analyzes legal matters, emphasizing the interpretation, application, and evaluation of relevant laws. Findings reveal restorative justice's benefits for victims, addressing their needs, enabling participation, and restoring their psychological and emotional well-being. Overall, restorative justice exhibits significant potential in protecting sexual violence victims. Hence, it necessitates serious attention to victim protection and a proper comprehension of restorative justice's principles and processes. With the appropriate context and careful preparation, this approach offers a more humane and comprehensive alternative for addressing sexual violence cases.